(untitled) (Publicaciones en Ciencias y Tecnología, 2013)
In this paper we present a generalization of the concepts of first and second F-variation (where F is a certain sequence of positive convex function defined on [0;+8], in the sense of Schramm-Riesz for normed space valued functions defined on an interval [a;b] c R. We characterized the functions of second F- variation in the sense of Schramm-Riesz, as those that can be expressed as the integral of a function of bounded F-variation in the sense of Schramm-Riesz.